Impact of Using Some Active Learning Strategies in a Curricula and Teaching Methods Course on the Learning Motivation Level and the Development of Critical Thinking Skills Among the Students of the Faculty of Arts at Al-Zaytoonah University - Abujreiban, Tahani (Journal of higher education theory and practice, 2024)
This study aimed at identifying the impact of using some active learning (AL)strategies in a Curricula and Teaching Methods Course on the learning motivation level and the development of Critical Thinking Skills among the Faculty of Arts at Al-Zaytoonah University (ZUJ) students. The study subjects were (61) male and female students selected from the Curricula and Teaching Methods Course of the Faculty of Arts at ZUJ. The study adopted the quasi-experimental approach. To answer the two questions of the study, the Learning Motivation Scale consisting of (35) paragraphs, and the Critical Thinking Skills Test consisting of (34) paragraphs were constructed. The study results revealed that there are significant differences between the means of the scores of the students of the Curricula and Teaching Methods course between the experimental group and the control group on the Learning Motivation Scale and the Critical Thinking Skills Test that can be attributed to using AL strategies. Therefore, the researcher recommended the use of learning outcomes related to learning motivation and critical thinking skills.